Pengaruh Kualitas Produk, Persepsi Harga, dan Citra Merek Terhadap Keputusan Pembelian (Studi Kasus pada Kosumen Maybelline Super Stay Matte Ink di Kota Semarang) - Oktavia Ayu Wulansari; Kristina Anindita Hayuningtias (Universitas Batanghari, 2023)
This study examines the effect of product quality, perceived price, and brand image on purchasing decisions. This research was conducted in the city of Semarang. The sampling method used purposive sampling and data collection using a questionnaire totaling 99 respondents. Relationships and influences between variables are explained using multiple regression analysis methods. The results showed that product quality, price perceptions and brand image had a positive and significant effect on purchasing decisions.